Animal Experiments of the Helical Flow Total Artificial Heart. Issue 8 (August 2015) - Abe, Yusuke; Isoyama, Takashi; Saito, Itsuro; Inoue, Yusuke; Ishii, Kohei; Sato, Masami; Hara, Shintaro; Yurimoto, Terumi; Li, Xinyang; Murakami, Haruka; Ariyoshi, Koki; Kawase, Yukino; et al.
Abstract Severe cardiac failure patients require a total artificial heart (TAH) to save life. To realize a TAH that can fit a body of small stature and has high performance, high durability, good anatomical fitting, good blood compatibility, and physiological control, we have been developing the helical flow TAH (HFTAH) with two helical flow pumps with hydrodynamic levitation impeller. Animal experiments of the HFTAH were conducted to perform in vivo studies. The HFTAH was implanted in 13 adult female goats weighing 45.0–64.0 kg. After surgery, neither anti‐coagulant nor anti‐platelet medication was given systemically. The HFTAH was usually driven with a quasi‐pulsatile mode. The 1/R control or ΔP control was applied to control the circulation. The ΔP control is a new method using simplified equation of the 1/R control. The HFTAH could be implanted in all goats with good anatomical fitting. Two goats survived for a long time (100 and 68 days). Major causes of termination were device failure and surgical complications. In the device failure, trouble with hydrodynamic bearing was conspicuous. In the two long‐term survived goats, experiments were terminated with bearing instability that was probably caused by the suction effect. In these goats, hemolysis occurred on postoperative day 88 and 44, which was considered to be relevant to the bearing trouble. Thrombus was found at the broken right bearing of the 100‐day survived goat. However, antithrombogenicity of the pump is expected to be good unless bearing trouble occurs. In two long‐term survived goats, the 1/R control or ΔP control worked appropriately to prevent the elevation of right atrial pressure. In both goats, hemodynamic parameters changed with the condition of the animals, liver and kidney functions remained almost normal except when recovering from surgery and during hemolysis, and total protein recovered 2 weeks after surgery. Although instability of the hydrodynamic bearing should be improved, performance of the HFTAH with physiological control could be demonstrated.